STEMI Equivalents and Their Incidence during EMS Transport. (2nd January 2022) - Palladino, Nicholas; Shah, Aman; McGovern, Jeffrey; Burns, Kevin; Coughlin, Ryan; Joseph, Daniel; Cone, David C.
Abstract: Objective: The management of patients with ST-elevation myocardial infarction (STEMI) is time-critical, with a focus on early reperfusion to decrease morbidity and mortality. It is imperative that prehospital clinicians recognize STEMI early and initiate transport to hospitals capable of percutaneous coronary intervention (PCI) with a door-to-balloon time of ≤90 minutes. Three patterns have been identified as STEMI equivalents that also likely warrant prompt attention and potentially PCI: Wellens syndrome, De Winter T waves, and aVR ST elevation. The goal of our study was to assess the incidence of these findings in prehospital patients presenting with chest pain. Methods : We conducted a retrospective chart review from a large urban tertiary care emergency department. We reviewed the prehospital ECG, or ECG upon arrival, of 861 patients who were hospitalized and required cardiac catheterization between 4/10/18 and 5/7/19. Patients who had field catheterization lab activation by EMS for STEMI were excluded. If a prehospital ECG was not available for review, the first ECG obtained in the hospital was used as a proxy. Each ECG was screened for aVR elevation, De Winter T waves, and Wellens syndrome. Results : Of 278 charts with prehospital ECGs available, 12 met our criteria for STEMI equivalency (4.4%): 6 Wellens syndrome and 6 aVR STEMI. There were no cases of De Winters T waves. Of 573 charts with no prehospital ECG available, 27 had initial hospital ECGs that met our STEMI equivalent criteria (4.7%): 7 Wellens syndrome and 20 aVR STEMI. Again, there were no cases of De Winters T waves. Conclusions : These preliminary data suggest that there are significant numbers of patients whose prehospital ECG findings do not currently meet criteria for field activation of the cardiac catheterization lab, but who may require prompt catheterization. Further studies are needed to look at outcomes, but these results could support the need for further education of prehospital clinicians regarding recognition of these STEMI equivalents, as well as quality initiatives aimed at decreasing door-to-balloon time for patients with STEMI equivalents.